201 knockout answers to tough interview questions the ultimate guide to handling the new competency-based interview style - Matias, Linda (IG library, 2010)
Increasingly, employers today are using a tough new kind of interview to evaluate candidates and determine how well they think on their feet. To be successful in these new competency-based interviews, job seekers must be prepared with situation-specific examples that highlight the accomplishments, knowledge, and abilities they have that employers need. Featuring a plethora of sample questions and winning answers. This indispensable guide features fill-in-the-blank exercises readers can use to prepare themselves to demonstrate sought-after competencies and wow potential employers. It's a powerful book no job seeker should be without.